PEOPLE AND KNOWLEDGE MANAGEMENT AS COMPETITIVE AND PRODUCTIVE DIFFERENTIALS IN ORGANIZATIONS - Freitas de Oliveira, Camila (Revista Interface Tecnológica, 2021)
Studies on PeopleManagement and Knowledge Management in organizations point to them as decisive factors in competitiveness in the current globalized market. The enabling conditions provided by good people management and knowledge management, allow organizations to have an idea of ​​how to increase the creation and dissemination of knowledge in order to maintain competitive advantage. This work will aim to understand the new logic of people management in organizations in search of knowledge and the new roles that workers assume in this context as a competitive differential. Through bibliographic research, the concepts of people management, knowledge management, intellectual capital and successful examples of good management in this topic were presented. In the end it was possible to verify that the organizations understand that the management of people when well executed becomes a competitive differential in several sectors.